Structural, optical, vibrational and photoluminescence studies of Sn-doped MoO3 sprayed thin films - YUMAK YAHŞİ, AYŞE (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
MoO3 thin films were deposited on glass substrates by a simple mini spray technique. Alternatively, some of the obtained films were doped with tin at the molar rates of: 1-4%. In addition to the structural investigations, the opto-thermal studies, Raman spectroscopy and photoluminescence measurements were investigated. Structural studies show that all MoO3:Sn thin films crystallized in orthorhombic phase with noticeable changes in terms of Sn level. In the same line, Raman spectroscopy reveals the principal MoO3 vibration's mode with the shift related to Sn incorporation in MoO3 matrix. Optical parameters, such as optical band gap, Urbach energy, refractive indices and dielectric constants were studied in terms of Sn doping level. For all MoO3:Sn prepared films, PL measurements show three large bands located at 371.5, 485.5 and 729 nm. Additional analyses within the Lattice Compatibility Theory LCT provided also tangible explanation to some tin incorporation patterns within MoO3 matrix. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Molybdenum oxide; Sn doping; Urbach tailing; LCT; Raman spectroscopy; PL measurements; COMPATIBILITY THEORY LCT; SUBSTRATE-TEMPERATURE; PHYSICAL-PROPERTIES; RAMAN-SPECTRA; ZNO; OXIDE; PATTERNS; PERFORMANCE; ALPHA-MOO3; CONSTANTS